Desenvolvimento de um sistema de detecção de continuidade elétrica em cabos de baixa tensão - Soares, Gesiel (2014)
This work deals with the development of a measurement device in area of low voltage, which serves to verify the electrical continuity in conductors. In comparison with existing systems for this type of measurement it has innovation in the fact of not having electric physical reference systems. The system consists on two circuits powered by batteries, wherein: one of these supply a square wave generates a variation of potential and the other amplifies low amplitude sensing the change of this potential, but both are electrically independent. For electrical independence can be understood that the reference, also called ground or battery negative, of a circuit is not connected to another.